Giant cell arteritis: incidence and phenotypic distribution in Western Norway 2013–2020 - Skaug, H. K.; Fevang, B. T.; Assmus, J.; Diamantopoulos, A. P.; Myklebust, G.; Brekke, L. K. (Frontiers in Medicine, 2023)
Objectives: There is an increasing awareness of the spectrum of phenotypes in giant cell arteritis (GCA). However, there is sparse evidence concerning the phenotypic distribution which may be influenced by both genetic background and the environment. We established a cohort of all GCApatients in the Bergen Health Area (Western Norway), to describe the phenotypic distribution and whether phenotypes differ with regards to incidence and clinical features.Methods: This is a retrospective cohort study including all GCA-patients in the Bergen Health Area from 2013-2020. Data were collected by reviewing patient records, and patients considered clinically likely GCA were included if they fulfilled at least one set of classification criteria. Temporal artery biopsy (TAB) and imaging results were used to classify the patients according to phenotype. The phenotype "cranial GCA" was used for patients with a positive TAB or halo sign on temporal artery ultrasound. "Non-cranial GCA" was used for patients with positive findings on FDG-PET/CT, MRI-, or CT angiography, or wall thickening indicative of vasculitis on ultrasound of axillary arteries. Patients with features of both these phenotypes were labeled "mixed". Patients that could not be classified due to negative or absent examination results were labeled "unclassifiable".Results: 257 patients were included. The overall incidence of GCA was 20.7 per 100 000 persons aged 50 years or older. Overall, the cranial phenotype was dominant, although more than half of the patients under 60 years of age had the non-cranial phenotype. The diagnostic delay was twice as long for patients of non-cranial and mixed phenotype compared to those of cranial phenotype. Headache was the most common clinical feature (78% of patients). Characteristic clinic features occurred less frequently in patients of non-cranial phenotype compared to cranial phenotype.The overall incidence for GCA was comparable to earlier reports from this region. The cranial phenotype dominated although the non-cranial phenotype was more common in patients under 60 years of age. The diagnostic delay was longer in patients with the non-cranial versus cranial phenotype, indicating a need for examination of non-cranial arteries when suspecting GCA.